The Timid Corporation: Why Business Is Terrified of Taking Risk - Benjamin Hunt (UK Wiley, 2003)
This book looks at changing managerial styles in business and the predominance of risk aversion behavior over risk taking behavior. The author explores the various reasons (regulation and media scrutiny among them) that corporations are becoming more timid and analyzes the consequences this could have on the future of innovation and technological development in the business future.
Keywords: Corporations; Business; Nonfiction; Global Citizenship (BIN1064-N)